Pengaruh Likuiditas terhadap Profitabilitas pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia - Serli Bin Yustin; Hariany Idris; Azwar Anwar (Pusat Riset dan Inovasi Nasional, 2026)
This study aims to evaluate the correlation between profitability and liquidity levels among pharmaceutical issuers on the Indonesia Stock Exchange (IDX) throughout the 2019-2023 period. The researcher employs the Current Ratio (CR) as the indicator for liquidity (independent variable), while Return on Investment (ROI) represents profitability (dependent variable). Using a purposive sampling approach, 7 out of 13 companies within the population were selected as subjects of observation. The data were processed using simple linear regression methods, hypothesis testing, and the fulfillment of classical assumption requirements. The research findings conclude that the current ratio has a positive and significant influence on return on investment. In practical terms, this phenomenon illustrates that the better a company's capacity to settle its short-term debt, the more its effectiveness in generating investment profits increases. These results align with the principles of trade-off theory regarding the urgency of stability between liquidity and profitability aspects to maintain sustainability and operational efficiency. Based on the coefficient of determination test, the liquidity variable contributes 32% to the fluctuations in profitability. The output of this research is projected to serve as strategic consideration for management in optimizing current asset management, as well as a reference for future academic studies